Psychological principles of communication in creating management teams - Cherkassky Аndrey (Psychological Prospects Journal, 2021)
Purpose. The purpose of the article is to consider and analyze the basic principles and theoretical models of communication in management teams. Methods. The research is based on theoretical methods: analysis and generalization of scientific sources on the problems of studying communication in management teams. Results. The article presents the main definitions of the concept of "communication" in modern science, analyzes the communication processes that ensure effective team work. It is noted that interpersonal communication, information exchange, that is, communication between team members, acts as the basis for direct association of people in the interests of obtaining a synergistic effect from joint activities. Special emphasis is placed on the fact that the ability of people to communicate with each other, that is, to establish communication channels, is not the only condition for creating teams. For teams, it is important for them to form a set of their own norms and rules of joint work, the role structure of performing duties, a special organizational culture and management style, etc.However, all of them can be developed by a team only if there is a well-formed communication system between its participants. Thus, teams build a more powerful network of communication channels, both in terms of branching and the amount of information that passes through them. In modern conditions, the ability of teams to create a communication system is one of their key competencies, and the most important condition for forming the communication potential of a team is the trust of its participants in each other. Creating an atmosphere of trust in the team is an important component of building and developing a communication network, the formation of communication diffusion, the absence of which will actually become an insurmountable obstacle to the creation of teams ’ common human potential, the transformation of personalized knowledge into Team knowledge. The conclusions indicate that team communication allows not only to ensure the best implementation of the knowledge, skills and abilities of each team member in their workplace, but also to form a mechanism that provides flows of ideas, knowledge and observations that one team member has to all their colleagues. It is emphasized that it is important to train team leaders, all management personnel, and train methods for establishing communication channels, both horizontally and vertically.